Studi Pengaruh Medan Radio Frekuensi (RF) pada Minyak Goreng - Firdausi, K. Sofjan; Istianah, Istianah; Marhaendrajaya, Indras (BERKALA FISIKA, 2008)
A study of non linier optic has been carried out for palm oil induced by RF frequency field,e using white light and laser light. The e’s value is produced by RF generator with 2kV of voltage and in the range of frequency between 6.04 MHz and 11 MHz. In this research, he-ne laser with 632.8 nm of wavelength, green pointer laser with 532 nm of wavelength and white light of halogen with maximum power 130, are used as source of light. The physical characteristics observed in the experiment are change of light polarization that is transmitted through palm oil. From experiment result indicates that the change of polarization angle is not linearly dependent on e, At the same condition, the highest changes of polarization angle takes place when providing green laser, upright position of RF frequency field on polarization angle direction 900 for the twice used-palm oil. Keywords: non – linier optics, polarization angle, RF frequency field